A review of phytoconstituents and their pharmacological properties of Andrographis Paniculata (NEES) - DR. RUCHI ACHARYA (International Journal of Pharma and Bio Sciences, 2017)
Medicines in India are used by about 60 per cent of the world’s population. Traditional medicines are not only used for primary health care not just in rural areas in developing countries, but also in developed countries as well where modern medicines are predominantly used. While the traditional medicines are derived from medicinal plants, minerals, and organic matter, the herbal drugs are prepared from medicinal plants only. Since many diseases commonly treated with Andrographis paniculata in traditional medical system and are consider self limiting. The major objective of this review is providing a link among researchers working in a several disciplines associated with medicinal plants. This review paper also highlighted on evaluation and characterization of various bioactive phytoconstituents against various diseases based on their traditional asserts of the plants given in Ayurveda. In this review the Andrographis paniculata reported as having antimicrobial, anti bacterial, anti HIV, anti cancerous, hepatoprotective activity, anti diabetic, antioxidant activity etc.